COMPENSATION FOR THE PUBLIC SERVICE FOR WAR TIME AND DISCRIMINATION AS FACTORS FOR MARGINALISTAION OF WAR VETERANS - Marković-Savić, Olivera (Political Review, 2023)
War participation is an intense psychosomatic deprivation. The consequences may range from war trauma to the loss of physical ability. As a result, war veterans upon returning from war may suffer civil life adaptation issues, and are at a high risk of marginalization. States accommodate the consequences of this process by creating various means of looking after this population. Previous research, although minor in scope, reveals the lack of looking after this population and shows the discontent of this population towards the ways the state and civil society treat them. The text is searching for an answer to the question whether the war veterans in Serbia may be considered a marginalized group and why this is the case. The conclusion is that the war veterans are indeed marginalized for not receiving appropriate compensation for the public service at the most perilous time; furthermore, there is discrimination within the war veteran community itself. The experience of marginalization is both formal and subjective. The formal marginalization is manifested in the lawsuit filed to the European Court of Human Rights; and the subjective marginalization is present in the stereotypes and labeling attitudes from the public, and in state institutions, too. Modern discourse treats the definition of equality increasingly less frequently as a wealth distribution inequality, and more often as equal opportunities for all. Therefore, besides considering economic inequality, it is vital to establish more egalitarian relationships towards the social and cultural acceptance of the otherness. Above all, war veterans require appreciation, even more than the welfare assistance in the form of the so-called “war wages”. This holds the state responsible towards the citizens that have done their public service in defending the territorial integrity and sovereignty of the state.
Keywords: war veterans; public service compensation; discrimination; marginalization